Proton-coupled electron transfer in a hydrogen-bonded charge transfer complex - Verma, Sandeep; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry B, 2016)
A proton-coupled electron transfer (PCET) reaction in a hydrogen bonded charge-transfer (CT) complex of 4-([2,2'-bipyridin]-4-yl)phenol (bpy-phenol) with a F- ion has been investigated by ultrafast time-resolved transient absorption spectroscopy. The phenolic receptor molecule, bpy-phenol, binds to the F- ion through a hydrogen bond and senses the F- ion-via the Stokes-shifted CT band. Upon photoexcitation, CT from the phenol residue to the bpy residue promotes proton transfer from the phenol radical cation (ArOH center dot+) to the fluoride ion at ultrafast time scales of <150 fs (instrument response function limited) and 3 ps, separately. The fast and slow proton-transfer times are linked to two different types of hydrogen-bonding networks between the phenol residue and fluoride ion. Crystalline water in the fluoride salt hydrates mediates the proton-transfer reaction. This work demonstrates the participation of a hydrogen-bonded water bridge within a PCET reaction in a water restricted environment.